A manifestação dos estados de violência no discurso jornalístico - Cano, Márcio Rogério de Oliveira (2012)
This research is about how the state of violence, guided by a discourse of violence, constitutes interdiscoursively, journalistic discourse. To this end, the aim of this research is to show how the discourse of violence ends impregnating the journalistic discourse, promoting a series of states of violence. The theme appears to be of great social and academic relevance, as it contributes to the studies about a phenomenon of great social concern, which is violence, as well as the importance of the need to seek ways to understand the traits of a violence that in one dimension is more subtle, than the deeds of violence, who are in a more concrete dimension. We start, therefore, from the thesis that the discourse of violence is a discourse of violence atopic, who lives on the fringes of society, permeating other discourses in the ways of dealing with each other, but that can be apprehended by the mechanisms of discourse analysis, especially the principles the scenery and the discursive ethos. To accomplish this research, we formed a corpus of five scenes selected during the doctorate process, from Folha de S. Paulo newspaper and Veja magazine. This corpus was analyzed in the light of the scene of enunciation, divided in global and generic scene and scenography; the discursive ethos of the speaker and the stereotypical ways of representing the other in discourse. The theoretical framework adopted in this research was discourse analysis conception, mainly the works of Dominique Maingueneau. To discuss the state of violence, we adopted mainly Yves Michaud, and for the considerations about the journalistic discourse, the concepts of Marcondes Filho, Medina and Charaudeau. As a results, This study showed that there is a discourse of violence and it is atopic and outside of the other topics and paratopics discourses but, through the interdiscourse, it impregnates the journalistic discourse and makes it, in the way of the scenery and the discursive ethos, commit yourself a series of states of violence against a lot of groups and social actors, using the stereotypical traits that lie in the discursive memory of discursive communities to treat each other violently. This discourse of violence is the traces of the positioning of the speaker may or may not be adhered to by the co-enunciator, making this type of violence be perpetuated